PUBLIC ADMINISTRATION OF SUSTAINABLE DEVELOPMENT OF RURAL TERRITORIES - КОМАХА, Лариса; КОЛТУН, Вікторія (Київський національний університет імені Тараса Шевченка, 2024)
Background . This article is focused on specifics of sustainable development of rural territories as a milestone on the way to harmonious regional development. Notably, dynamics and realities of rural territories challenge sustainable development and require some ways to maintain it. There is evident asymmetry between sustainable development of rural and urban territories, and the government has to take measures to ensure equal access to resources and opportunities for those territories to unleash their potential. Methods . In the preparation of the research, both general methods, including methods of abstraction, logic, synthesis and analysis (in particular, causal analysis), extrapolation, and special methods and approaches were used. Thus, a chronological (historical) approach is used when analyzing trends in the development of rural areas compared to urban areas; a complex of methods belonging to a wide range of systems theory (when analyzing correlations between environments of different levels, connections, resources, dynamic open systems, analysis of homeostats of the specified systems); activity approach – when characterizing the reasons for the mobility of the rural and urban population; modeling – when making forecasts of the development of territories. Results . The social aspect of sustainable development of rural territories endeavors to strengthen the ties between public authorities and community stakeholders in order to find the integral solutions consistent with dynamics of the relevant regions and capable of taking the challenges. The environmental aspect outlines the land use conflict arising out of the economic activities in the relevant areas of interest. The economic aspect has to be seek economic equality and equal access to jobs for rural and urban population, as well as improve the quality of life for the villagers. Conclusions . The article identifies the new factors that have to be studied in the development models, for example, the ever-growing ties between city and village life, the economic activity changes emerging in the rural areas due to transfer from the traditional agriculture to secondary production and services. It has been proven that village and city relationship is a deciding factor governing sustainable regional development, because spatial differences between cities and suburban areas are growing, and therefore it is necessary to study regional development to analyze interlinkage between rural and urban territories

Вступ . Розглянуто специфічні аспекти сталого розвитку сільських територій як віхи на шляху до гармонійного регіонального розвитку. Зазначено, що динаміка та реалії сільських територій детермінують та уможливлюють сталий розвиток, вимагаючи водночас певних кроків з його підтримки. Підкреслено, що існує очевидна асиметрія між сталим розвитком сільських і міських територій і необхідно вжити заходів для забезпечення рівного доступу жителів до ресурсів і можливостей, що сприятиме розкриттю потенціалу вказаних територій. Методи . Застосовано як загальні методи, зокрема методи абстрагування, логіки, синтезу та аналізу (наприклад причиннонаслідкового аналізу), екстраполяції, так і спеціальні методи та підходи. Хронологічний (історичний) підхід використано під час аналізу тенденцій відставання у розвитку сільських територій відносно міських; комплекс методів, що належать до широкого кола теорії системи застосовано для аналізу кореляцій між середовищем різного рівня, зв'язків, ресурсів, динамічних відкритих систем, аналізу гомеостатів зазначених систем); діяльнісний підхід – під час здійснення характеристики причин мобільності сільського та міського населення; моделювання – під час прогнозування перспектив розвитку території. Результати . Виявлено, що соціальний аспект сталого розвитку сільських територій спрямований на посилення зв'язків між органами державної влади та зацікавленими сторонами громади з метою пошуку цілісних рішень, які відповідають динаміці відповідних регіонів і здатні протистояти викликам. Екологічний аспект окреслює конфлікт землекористування, що виникає унаслідок господарської діяльності у відповідних сферах інтересів. Економічний аспект має полягати в досягненні економічної рівності та рівному доступі до роботи для сільського та міського населення, а також покращенні якості життя у сільській місцевості. Висновки . Виокремлено нові обумовлені фактори, які потребують вивчення у моделях розвитку, такі як зв'язки, що все частіше виникають між сільським і міським світом, а також зміни в типах економічної діяльності, що розвиваються на сільських територіях, оскільки відбувається перехід від сільськогосподарської діяльності, яка є традиційною працею, до вторинної виробничої та обслуговчої діяльності. Доведено, що відносини між селом і містом є вирішальним фактором сталого розвитку регіонів, оскільки просторові відмінності між центрами та периферіями зростають, ці просторові нерівності вимагають досліджень регіонального розвитку для аналізу взаємозалежності між сільськими та міськими територіями.
ПУБЛІЧНЕ УПРАВЛІННЯ СТАЛИМ РОЗВИТКОМ СІЛЬСЬКИХ ТЕРИТОРІЙ
Keywords: sustainable development; economic aspect; environmental aspect; social aspect; rural territories; public administration; сталий розвиток; економічний вимір; екологічний вимір; соціальний вимір; сільські території; публічне управління.